2018
DOI: 10.15252/embr.201744722
|View full text |Cite
|
Sign up to set email alerts
|

Stress granules counteract senescence by sequestration of PAI‐1

Abstract: Cellular senescence is a physiological response by which an organism halts the proliferation of potentially harmful and damaged cells. However, the accumulation of senescent cells over time can become deleterious leading to diseases and physiological decline. Our data reveal a novel interplay between senescence and the stress response that affects both the progression of senescence and the behavior of senescent cells. We show that constitutive exposure to stress induces the formation of stress granules (SGs) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 82 publications
(189 reference statements)
5
46
0
Order By: Relevance
“…Results in yeast also extend to mammalian cells, where stress-induced stalling of translation leads to the condensation of protein and RNA into stress granules, which are dissolved after stress by Hsp110, Hsp70, and Hsp40 (8,75). Importantly, stress granules protect against cellular senescence by sequestering PAI-1, an established promoter of senescence (76). Overall, the ability of cells to form assemblages of proteins and nucleic acids in response to stress appears to be a conserved mechanism for cells to weather deleterious conditions.…”
Section: Cellular Fitnessmentioning
confidence: 93%
“…Results in yeast also extend to mammalian cells, where stress-induced stalling of translation leads to the condensation of protein and RNA into stress granules, which are dissolved after stress by Hsp110, Hsp70, and Hsp40 (8,75). Importantly, stress granules protect against cellular senescence by sequestering PAI-1, an established promoter of senescence (76). Overall, the ability of cells to form assemblages of proteins and nucleic acids in response to stress appears to be a conserved mechanism for cells to weather deleterious conditions.…”
Section: Cellular Fitnessmentioning
confidence: 93%
“…These results indicate that when cells enter the senescence state, two essential SG proteins, eIF2α and the transcription factor Sp1, can work as direct aging‐related targets, causing significant deficiencies in SG production. Similarly, a recent study found that constitutive exposure to stress could induce the formation of SGs in proliferating cells, but not in fully senescent human fibroblasts (Omer et al, 2018). It has also been reported that the formation of SGs during early stages of senescence is sufficient to prevent senescence.…”
Section: Relationship Between Stress Granules Aging and Aging‐relatmentioning
confidence: 82%
“…Plasminogen activator inhibitor‐1 (PAI‐1), an activator of senescence, is also localized to SGs in senescent cells. This indicates that SGs can counteract senescence by recruiting a key factor to the SGs and disrupting its senescence function (Omer et al, 2018).…”
Section: Functions Of Stress Granulesmentioning
confidence: 99%
See 2 more Smart Citations